The Effect of Almond Milk on Tooth Enamel Surface Hardness - Haniyah Fakhirah; Danica Anastasia; Rini Bikarindrasari (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2022)
Introduction: Enamel is the hardest substance in the human body and serves as the wear-resistant outer layer of the dental crown. Demineralization releases mineral ions which cause a decrease in the enamel surface hardness. Demineralization could be neutralized to recover minerals, and this process is called remineralization. Almond milk was an alternative to cow’s milk, supporting tooth enamel surface remineralization. Purpose: To determine the effect of almond milk on enamel hardness. Methods: Twenty maxillary premolars were divided into group A (control) and group B (almond milk). Before treatment, samples were soaked in 1% citric acid. Enamel hardness was tested with Vickers Hardness Tester. The statistical tests used in this study were Paired t-test and Independent Sample t-Test. Results: The results of the paired sample test got significant results in groups A and B in the comparison of pretest - 1% citric acid, and 1% citric acid - posttest, which means that there was a significant difference in enamel hardness values. However, the results obtained were not substantial in groups A and B in the posttest- pretest comparison. There was no significant difference between Group A and Group B in the independent sample test results. There was an increase before and after, but it was not much different when compared to the control. Conclusion: Almond milk can increase enamel surface hardness but cannot reverse the initial enamel surface hardness value.